Discovery and application of food catalysts to promote the coupling of PQQ (quinone) with amines - Ikemoto, Kazuto; Imaruoka, Satoko; Ishak, Nur Syafiqah Mohamad (Frontiers in Nutrition, 2024)
Background: Biocatalysts (enzymes) play a crucial role in catalyzing specific reactions across various industries, often offering environmentally friendly and sustainable alternatives to chemical catalysts. However, their catalytic activities are susceptible to denaturation. In this study, we present the discovery of novel protein-based biocatalysts derived from processed foods, including skimmed milk, soy milk, cheese, and dried tofu. These food catalysts exhibit high availability, low cost, safety, and thermo-stability.Results: Focusing on the physiologically intriguing coenzyme pyrroloquinoline quinone (PQQ), we observed that the reaction with glycine to form imidazolopyrroquinoline (IPQ) did not proceed efficiently when PQQ was present at very low concentrations. Surprisingly, in the presence of protein-based foods, this reaction was significantly accelerated. Notably, skimmed milk enhanced the PQQ detection limit (600 times lower) during high-performance liquid chromatography (HPLC) following IPQ derivatization. Milk appears to facilitate the reaction between PQQ and various amino acids, primary amines, and secondary amines. Further investigations revealed that food catalysis operates through a non-enzymatic mechanism. Additionally, nuclear magnetic resonance spectroscopy demonstrated that milk components interacted with amino substrates due to the ability of amines to react with quinones on colloidal surfaces.Conclusion: These practical food catalysts not only contribute to environmental safety but also hold significance across diverse scientific domains. Non-enzymatic protein catalysts find applications in biocatalysis, organic synthesis, food technology, analytical chemistry, and fundamental nutritional and evolutionary studies.